The Effects of a 30-Minute Napping Opportunity after a Night of Partial Sleep Denied on Cognitive and Short-Term High-Intensity Performance and Mood States - Ayhan, Savaş (Pakistan Journal of Medical & Health Sciences, 2022)
Background: It is suggested that there is a relationship between a 30-minute napping opportunity after a night of partial sleep denied on cognitive and short-term high-intensity performance and mood states. Aim: The purpose of this study was to look at the effects of a 30-minute nap on cognitive and short-term high-intensity performance, as well as mood states, following a night of partial sleep deprivation. Methods: On a voluntary basis, 15 elite male athletes took part in the study. The study was carried out as a quantitative study using an experimental design with pre-test and post-test groups. After four weeks of training on five days a week, the athletes were given a 30-minute nap (laying down) between 13:00 and 15:00. The Pittsburgh sleep quality index, vertical jump test, and pulmonary function test were administered to the athletes who napped at 17:00. The Shapiro-Wilk Normality Test was used to determine the data's normality distribution. In accordance with the experimental model and research design, the differences between measurement results were determined using the paired samples t-test (paired samples t-test). The threshold for significance was set at p0.05. Results: Maximum anaerobic power (W), average anaerobic power (W), minimum anaerobic power (W), vertical jump (cm), FVC(L), FEV1(L), FEV1/FVC (%) and FEF25 of the athletes participating in the research. A significant difference was determined between -75(L/s) pre-test values and post-test values (p<0.05). Athletes' anaerobic power (W), average anaerobic power (W), minimum anaerobic power (W), vertical jump (cm), FVC(L), FEV1(L), and FEF25-75 (L/s) post-test The athletes' FEV1/FVC (percent) post-test values were higher than the pre-test values and lower than the pre-test values (p0.05). Conclusion: As a result, short nap sessions have anaerobic power. It has been demonstrated that it improves respiratory functions and vertical jump parameters.